Turbine Design and Optimization for Energy Harvesting from Underground Water Pipe Sources: A Renewable Energy Approach - ROSDI BIN MOHD NOR, MUHAMAD ARIF HAZIQ BIN ROSDI; Zuliazura Mohd Salleh (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study investigates the hydro turbine design optimization for energy extraction from underground water pipes in Malaysian industry. The overuse of fossil fuels has led to economic, environmental, and sustainability concerns, necessitating the development of alternative energy resources. This study investigates the optimization of the hydro turbine blade angle for optimum energy efficiency at realistic underground pipe flow conditions. Three blade angles of 40°, 50°, and 60° were created in SolidWorks and investigated using Computational Fluid Dynamics (CFD) simulation in ANSYS Fluent. The study measured pressure distribution, velocity, RPM, and efficiency for optimal performance. The findings indicate that the 50° blade angle design provides an optimal balance between RPM and energy efficiency, minimizing turbulence and maximizing energy conversion. This optimum design has the potential for the installation of small-scale hydro turbines in existing industrial infrastructure, offering a renewable and inexpensive option to fossil fuels. The findings of this study are in line with Malaysia’s energy transition plans by incorporating renewable technology into industrial systems.